New routes for roads: using recycled greenhouse films to modify bitumens. (16th April 2007) - Gonzalez, O.; Munoz, M.E.; Santamaria, A.; Garcia-Morales, M.; Navarro, F.J.; Partal, P.
Four recycled greenhouse films made of low density polyethylene and EVA copolymer, are mixed with 6070 penetration grade bitumen. The goal is to improve the viscoelastic properties of bitumen used as a binder in road pavement, contributing to an environment improvement by reducing plastic waste. It is observed that a reasonable stability and a satisfactory upgrading face to rutting defect at high temperatures, can be achieved. The presence of a low amount of carbon black in two of the films does not alter the results. The content of film in bitumen/film blends is limited by stability problems (coalescence and creaming), as well as lack of flow capacity for pumping and mixing.